Daddy : stories - Cline, Emma (Random House, 2020)
"An absentee father collects his son from boarding school after a shocking act of violence. A nanny to a celebrity family hides out in Laurel Canyon in the aftermath of a tabloid scandal. A young woman sells her underwear to strangers. A notorious guest arrives at a placid, not-quite rehab in the Southwest. In ten remarkable stories, Emma Cline portrays moments when the ordinary is disturbed, when daily life buckles, revealing the perversity and violence pulsing under the surface. She explores characters navigating the edge, the limits of themselves and those around them: power dynamics in families, in relationships, the distance between their true and false selves. They want connection, but what they provoke is often closer to self-sabotage. What are the costs of one's choices? Of the moments when we act, or fail to act? These complexities are at the heart of Daddy, Emma Cline's sharp-eyed illumination of the contrary impulses that animate our inner lives"--